Efektivitas Pemanfaatan CODAP Terhadap Kemampuan Representasi Matematis Siswa pada Materi PLSV - Neneng Anastasyia; Eunike Ester Mataheru; Pieter Zakarias Tupamahu; Nawwir Junari (Universitas Ma'arif Lampung, 2026)
This study aims to examine the effectiveness of using CODAP on students’ mathematical representation ability in the topic of Linear Equations in One Variable. This study employed a quantitative design with a pre-experimental approach using a one-group pretest-posttest design. The research subjects were 19 eighth-grade students at Pattimura University Laboratory Middle School. The instrument used was an essay test designed to measure three indicators of mathematical representation ability: verbal-contextual representation, visual/graphical representation, and symbolic representation. The data were analyzed descriptively and inferentially using percentage scores, N-Gain, the Shapiro–Wilk normality test, the paired sample t-test, the Wilcoxon signed-rank test, and effect size analysis. The results showed that CODAP-assisted learning improved students’ abilities across all measured indicators. Verbal-contextual representation increased from 80.89 to 96.84, with an N-Gain of 0.483; visual/graphical representation increased from 47.37 to 86.84, with an N-Gain of 0.556; and symbolic representation increased from 0.00 to 56.21, with an N-Gain of 0.562. All improvements were categorized as moderate, yet they were statistically significant, with large to very large effect sizes. These findings indicate that CODAP helps students interpret contextual problems, read graphical representations, and construct mathematical models more meaningfully in the topic of linear equations in one variable.